Stabilization of a Class of Linear Systems With Input Delay and the Zero Distribution of Their Characteristic Equations - Zhou, Bin; Lin, Zongli; Duan, Guang-Ren (IEEE transactions on circuits and systems. I, Regular papers, 2011)
This paper is concerned with stabilization of linear systems with arbitrarily large but bounded time-varying delay in the input. A pole assignment based low gain feedback design is adopted to solve the problem. Both delay-dependent and delay-independent results are presented and a series of sufficient conditions for guaranteeing the stability of the closed-loop system are established. By using properties of this class of low gain feedback laws and the properties of certain transcendental equations, distribution of the zeros of the closed-loop characteristic equation is described. As a result, a necessary and sufficient condition is identified that guarantees the stability of the closed-loop system. A numerical example is given to illustrate the effectiveness of the proposed approach.